2013
DOI: 10.1016/j.jval.2013.08.1490
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Tocilizumab in Rheumatoid Arthritis, in Colombia

Abstract: Objectives: Several technologies are currently being developed for better stratifying individuals at risk of developing Rheumatoid Arthritis (RA) to patienttailored treatment. We assessed the potential cost-effectiveness of four technologies (MRI, il6-serum test, RNA B-cell signature, genetic assay) applied to patients with intermediate risk for RA (3-5 points on ACR/EULAR) using an one-year horizon. MethOds: The cost-effectiveness was simulated with a decision model using data from the Rotterdam Early Arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although these guidelines can improve cervical cancer detection and prevention, screening services can be costly, with costs varying widely due to screening under-use and inadequate use (3,(11)(12)(13)(14)(15). A previous study has identified an excess cost of $166,100 over 5 years for each ineligible woman (e.g., <21 and >65 years or those with a hysterectomy) who underwent screening (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although these guidelines can improve cervical cancer detection and prevention, screening services can be costly, with costs varying widely due to screening under-use and inadequate use (3,(11)(12)(13)(14)(15). A previous study has identified an excess cost of $166,100 over 5 years for each ineligible woman (e.g., <21 and >65 years or those with a hysterectomy) who underwent screening (15).…”
Section: Introductionmentioning
confidence: 99%